The Fukushima Daiichi Accident: The International Community Responds - Stephen G. Burns (Washington University Global Studies Law Review, 2012)
The accident at the Fukushima Daiichi nuclear power plant site in northeastern Japan has led to a worldwide focus on the safety of nuclear power and a renewed debate over its role in the generation of electricity. In the decade before the accident, interest in nuclear energy returned in the face of growing demand for electricity coupled with increased attention to reducing carbon emissions. These factors fostered what many call a “nuclear renaissance.” But, as the accident at the Fukushima Daiichi site unfolded in March 2011, the question seemed to become whether nuclear energy had any future at all. Although not as severe in terms of radioactive releases as the 1986 Chernobyl accident, the accident at the Fukushima Daiichi was significant and the only multi-unit accident in the history of nuclear power generation.
Keywords: nuclear energy law; energy law; international law